A REVIEW OF MECHANOCALORIC REFRIGERATION DEVICES FROM 2012 TO 2020 - Foleis, G. L.; Colman, F. C.; Oliveira, J. C. D. de (Revista de Engenharia Térmica, 2022)
Solid-State room temperature refrigeration devices have been reported extensively in the last decades with a focus on magnetocaloric effect materials, a thermal response to an applied magnetic field in a solid refrigerant. Currently, the limitations to generate large magnetic fields needed for better efficiencies have posed a challenge to rival current standard vapor compression cycles. Conventional refrigerants in standard vapor cycles are expected to contribute to global warming close to 25000 kgCO2,eq over the next 100 years. The need to overcome such challenges has driven a search for alternative i-caloric effects such as electrocaloric which is the thermal response of the material to the application of an electric field and mechanocaloric, a thermal response to the application of a stress field. Recently, the latter effect is being reported and categorized by the type of stress field applied. They are named elastocaloric for uniaxial stress, barocaloric for isostatic stress, and torsiocaloric for pure shear. Due to its simple stress, elastocaloric regenerators with shape memory alloys (SMA) were reported first. With a design similar to shell-tube heat exchanger with SMA being the shell and tubes while the heat transfer fluids (HTF) flows within the tubes. Promising thermodynamic cycle parameters such as coefficient of performance COP 11.0 with a temperature span of 24.6 K subject to a strain of 4.5% have been achieved with this design. Another device was reported working in a continuous non-regenerative manner with steady state being reached within seconds presented COP of 9.5 and a heat load of 250 W for a temperature span of 10K. As for barocaloric materials some researchers announced that are currently developing devices with these phenomena. Its main challenge is to elaborate a design that allows cyclic isostatic stress application, usually achieved by encapsulating the barocaloric material. One research group presented a study on a simulated active barocaloric regenerator on metal alloys and Acetoxy Silicone Rubber (ASR). The most recent mechanocaloric effect is the torsiocaloric. Two devices for measuring the torsiocaloric effect where presented, one in a batch form and another setup similar to a heat exchanger shell-tube where the tube is the solid-state refrigerant that can be twisted while in direct contact with the HTF flowing on the shell side. Thus, we aim to provide an in-depth analysis of recent studies of mechanocaloric devices describing their working cycles, thermodynamic parameters, HTF circuits and comparing their design choices, and forecast the design of near future mechanocaloric solid-state devices.